2005
DOI: 10.1063/1.1944727
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon absorption in solution by means of time-dependent density-functional theory and the polarizable continuum model

Abstract: We present the first study of two-photon absorption (TPA) of solvated molecules based on direct evaluation of TPA cross sections from the quadratic response of time-dependent perturbations. A set of prototypical two-photon (TP) chromophores has been selected and analyzed: a pure pi system (t-stilbene) and its substituted homologs obtained employing a donor (D) and an acceptor (A) group to probe the solvent effects along the series pi, D-pi-D, A-pi-D, and A-pi-A. For the selected systems we have calculated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
106
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 76 publications
(68 reference statements)
3
106
1
1
Order By: Relevance
“…͑4͔͒ is twice the Birge's formula. In summary, it is expected that our results for the 2PA cross-sections would differ by the factor of two in total, i.e., twice smaller, from the results of the works by Day et al 11 and Frediani et al 13 A second important aspect affecting the comparison between theoretical values for the 2PA cross-sections, and even between theoretical results and experimental data, is the distinct values used for the damping constant ⌫ f to describe the line broadening of the excited final state.…”
Section: -7mentioning
confidence: 76%
See 4 more Smart Citations
“…͑4͔͒ is twice the Birge's formula. In summary, it is expected that our results for the 2PA cross-sections would differ by the factor of two in total, i.e., twice smaller, from the results of the works by Day et al 11 and Frediani et al 13 A second important aspect affecting the comparison between theoretical values for the 2PA cross-sections, and even between theoretical results and experimental data, is the distinct values used for the damping constant ⌫ f to describe the line broadening of the excited final state.…”
Section: -7mentioning
confidence: 76%
“…For DIAMINO, Cronstrand et al 40 reported a value of 260 GM obtained using a few-state model and the B3LYP functional. More recently, Frediani et al 13 calculated a value of 765 GM for the higher energy transition of DIAMINO in vacuo. In spite of the energy difference ͑about 0.4 eV͒, we believe that the S 0 → S 3 transition determined in this work accesses the same 3 1 Ag state reported by Frediani et al 13 For DO3, a value of 84 GM was reported by Day et al 11 through a TDDFT/B3LYP study applying the two-state approximation and a Lorentzian line-shape for the S 0 → S 2 transition.…”
Section: -7mentioning
confidence: 99%
See 3 more Smart Citations